Normative data for lateral femoral cutaneous nerve SEPs - (:unkn) unknown (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2006)
Aims of the study. - To determine normative values for somatosensory evoked potentials (SEPs) of the lateral femoral cutaneous nerve (LFCN). Methods. - The LFCN was stimulated at two points, one located 1 cm lateral to the midpoint of a tine joining the anterior superior iliac spine (ASIS) and the patella (31 subjects), and the other one located 12 cm distal to the ASIS (24 subjects). Recordings were performed at C-z' (2 cm behind C-z) - F-z. Results. - Reproducible SEPs were obtained in all but one of the 31 subjects to ASIS-patella midpoint (mean P1 latency: 33.2 +/- 3.5 ms, mean side-to-side difference: 2.0 +/- 1.6 ms) and in all but three of the 24 subjects to stimulation 12 cm distal to the ASIS (mean P1 latency: 30.9 +/- 3.3 ms, mean side-to-side difference: 2.2 +/- 1.7 ms). Conclusions. - Reliable SEPs can be obtained to LFCN stimulation. It is easier and, therefore, more convenient to stimulate the ASIS-patella midpoint. (c) 2006 Elsevier SAS. ALL rights reserved.
Keywords: lateral femoral cutaneous nerve; somatosensory evoked potential; meralgia paresthetica; normative data; SOMATOSENSORY-EVOKED-POTENTIALS; MERALGIA-PARESTHETICA; ELECTRODIAGNOSIS